Global MPP Tracking for Photovoltaic Panel under Shading Conditions using Robust Numerical Algorithm - Mesbahi, Oumaima (2022)
This paper presents a new numerical approach for the modelling of the PV panels under partial shading conditions. It also solves the major drawback of the PV systems, which is the tracking of maximum power point under partial shading conditions where the P-V characteristic has a more complex structure with many local maximums on the graph. This paper aims to resolve this phenomenon using Newton method in order to find the global maximum power point.